Чисельне моделювання лінз типу "Риб'яче око Максвелла" за допомогою пакету МЕЕР - Новицький, В. В. (ХНУРЕ, 2021)
A gradient index (GRIN) lens is an example of an optical device whose focusing effect is realized by a spatial variation of the refractive index of the constituent material. We used the MEEP package for calculating electro-magnetic waves distribution in Maxwell Fishpond lens.
Keywords: градієнтна лінза; риб'яче око Максвелла; FDTD; MEEP